2007
DOI: 10.1128/jvi.01238-06
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Chlorotic Mottle Virus Is a Target of RNA Silencing but the Presence of Specific Short Interfering RNAs Does Not Guarantee Resistance in Transgenic Plants

Abstract: Tomato chlorotic mottle virus (ToCMoV) is a begomovirus found widespread in tomato fields in Brazil.ToCMoV isolate BA-Se1 (ToCMoV-[BA-Se1]) was shown to trigger the plant RNA silencing surveillance in different host plants and, coinciding with a decrease in viral DNA levels, small interfering RNAs (siRNAs) specific to ToCMoV-[BA-Se1] accumulated in infected plants. Although not homogeneously distributed, the siRNA population in both infected Nicotiana benthamiana and tomato plants represented the entire DNA-A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 89 publications
2
31
0
Order By: Relevance
“…We have also corroborated that the virus-associated siRNA populations are related to the entire genome although their concentrations are not homogeneous. Again, it seems that each virus or virus-host combination might present a particular pattern (14,36,45). For PepGMV, zones corresponding to transcripts of the Rep, TrAP, REn, and MP genes and both IRs seem to be preferential targets (hot spots) for a silencing mechanism in highly symptomatic tissue (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We have also corroborated that the virus-associated siRNA populations are related to the entire genome although their concentrations are not homogeneous. Again, it seems that each virus or virus-host combination might present a particular pattern (14,36,45). For PepGMV, zones corresponding to transcripts of the Rep, TrAP, REn, and MP genes and both IRs seem to be preferential targets (hot spots) for a silencing mechanism in highly symptomatic tissue (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Recent reports have shown that geminivirus-infected plants can recover or show reduction of symptoms (1,12,45). Such processes have been correlated to RNA silencing mechanisms.…”
mentioning
confidence: 99%
“…Although geminiviruses harbor a single-stranded DNA genome, they also are subject to transcriptional and posttranscriptional RNA silencing, as observed by the synthesis of geminivirus-specific siRNAs, (sRNA-directed) viral DNA methylation, and posttranscriptional gene silencing of protein-coding genes (14)(15)(16)(17). However, antiviral RNAi defense against geminiviruses is suggested to mostly rely on a methylation-based defense, a process that involves the action of siRNA-directed methylation pathway component Ago4 (18,19).…”
Section: Significancementioning
confidence: 99%
“…Genetic Engineering is most important technology for determining the resistance to field crops, whether it is found or not used by virus-derived genes that lead to the pathogen-derived resistance [79]. RNA Silencing is one of the most widely used methods to check the resistance in plants against the RNA viruses which is approximately used for more than 15 years [14, 64,74].…”
Section: Transgenic Mechanism As Silencing Suppressormentioning
confidence: 99%